Studies on electropolymerization of ortho-phenylenediamine on platinum microelectrode and its detection of hydrogen peroxide and ascorbic acid using electrochemical impedance spectroscopy / Aziah Ahmad Ariffin - Ahmad Ariffin, Aziah (2015)
Poly-ortho-phenylenediatnine (PoPD) has been successfully electropolymerized and characterized on Platinum disk (125 urn internal diameters) using Electrochemical Impedance Spectroscopy (EIS) and Cyclic Voltammetry (CY). oPD was first prepared using CV by dissolving oPD monomer into Phosphate Buffer Saline (PBS) using various monomer concentration, pH of PBS and scan rate to determine the optimum condition. The optimum condition (300 mM oPD in pH 7.2 PBS with scan rate 100 mVs⁻¹ ) recorded oxidation potential E =500 mV at the highest anodic peak current, 9.16 x 10⁵ mA cm⁻². Electropolymerization of oPD was carried out by EIS with applying the optimum condition and oxidation potential to determine the redox-kinetic parameters and electrical behavior of the system. Up to our knowledge, oPD electropolymerization on Pt disk microelectrode is firstly reported in this work. Theredox-kinetic parameters of PoPD obtained from impedance data are charge transfer resistance, Rct (1.80x 10² kΩ), diffusion coefficient, D, (1.23 x 10⁵ cms⁻¹) and double-layer capacitance, Cdl, (0.14 µf). These parameters were obtained as the impedance spectra were fitted to three proposed equivalent circuit models beginning with simple Randles Model, (R(Q[RW]) to a more complex models such as ([R(RQ)([RW]Q)] and [R([RW]C)(RC)]. They showed chi square values, X² , less than zero indicating the models tits to the impedance spectra. The PoPD coated electrode was used as analytical probes towards the detection of Hydrogen Peroxide (H₂O₂) and Ascorbic Acid (AA). EIS used to investigate the blocking ability of PoPO to the ascorbic acid and hydrogen peroxide is also firstly reported in this work. In various analytes concentrations., the impedance value of AA higher (4.4 kΩ to 6.6 kΩ) than H₂O₂ (2.8 kΩ to 3.7 kΩ) indicated the larger size of AA species impeded by PoPD layer to theelectrode surface compared with smaller size of H202 species allowed to permeate. Meanwhile, dielectric constant values were also determined from the impedance data and exhibited higher values for ascorbic acid compared hydrogen peroxide as well. PoPD formation onto the electrode surface was confirmed by FESEM by exhibited a rough and crater-like surface fanned.